Bioaktivitas Ekstrak Metanol Daun Pegagan (Centella Asiatica L.) Terhadap Pertumbuhan Bakteri Mycobacterium Tuberculosis - Yusran, Yusran; Ilyas, Asriani; Saleh, Asri (Al-Kimia, 2016)
Plants gotu kola (Centella Asiatica L .Urban) is a wild plant that efficacious as remedies traditional cure disease tuberculosis (TB).TB is disease contagious infection caused by bacteria mycobacterium tuberculosis. Research aims to understand the ability extract methanol leaves gotu kola red and leaves gotu kola green and determines the concentration optimal extract methanol leaves gotu kola red and leaves gotu kola green and to know the comparison between extract methanol leaves gotu kola red with an extract methanol leaves gotu kola green in inhibits the activity of mycobacterium tuberculosis.Extraction done with the methods maceration use methanol and continued with evaporation until obtained extract viscous .Testing antibacterial activity done in a microscopic observation drug susceptibility ( mods ) use plate petri dish 24 hole with the variation of concentration ie 20%,40%, 60%, 80% and 100%.The results of testing show that extracts methanol leaves gotu kola red and leaves gotu kola green positive capable of inhibiting the growth of bacteria mycobacterium tuberculosis with inhibition optimal in concentration 80 % and 100 % characterized by the absence of growth bacteria colonies which are (-) or 0 %.Extract methanol leaves gotu kola green capable of inhibiting the growth of bacteria mycobacterium tuberculosis better than extract methanol leaves gotu kola red seen in concentration 40% and 60%.